Identifikasi Gen elF4G asal Oryza rufipogon pada Padi Varietas Inpari HDB dan Inpari Blas - Ifa Manzila; Tri Puji Priyatno (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2015)
Wild rice accession Oryza rufipogon is known as a source of tungro resistance genes and has been used to develop tungro resistant varieties, especially against rice tungro spherical virus (RTSV). However the genes have not been identified yet. Previously, an eukaryotic Translation Initiation Factor (eIF4G) was identified as a putative gene associated with recessive resistance gene against RTSV in Utri Merah variety. The research was aimed to detect and identify the eIF4G gene on rice var.Inpari HDB and var. Inpari Blas using specific primer that was designed based on Utri Merah eIF4G gene sequences. The resistance respons of both Inpari varieties and O.rufipogon against 3 tungro virus isolates were conducted in the green house trial. Assays were done based on international rice testing nursery according to IRRI. The eIF4G gene is amplified by PCR and the amplicon was directly sequenced, then analysed in silico. The results showed that all 3 varieties are classified as resistant against tungro virus isolates. PCR was successfully amplified the eIF4G gene with size 300 bp in both of varieties and their parent O. rufipogon. The nucleotides homology of eIF4G among those 2 varieties and O. rufipogon is up to 100%, while the homology to Utri Merah was 93%. There were 4 nucleotides deletion and 16 nucleotides differences between Utri Merah and those 2 varieties and O. rufipogon, respectively. Those nucleotide differences lead to deletion of 1 amino acid and 4 amino acids different between both Inpari varieties and O.rufipogon in comparison with corresponding amino acid in Utri Merah.